STRUCTURAL EVALUATION OF FLEXIBLE PAVEMENT USING MANUAL PAVEMENT DESIGN 2017 METHOD AND ASPHALT INSTITUTE METHOD (Case Study : Road Pantura, Border of Pamanukan City ÃâÃâ Sewo) - FIRGITA PRATAMI - NIM : 26915007 , PUTRI
National road of PANTURA, section border of Pamanukan city – Sewo is national roads with high traffic volume, so road maintenance needs to be done such as overlay thickness. Two methods are used for the calculation of overlay thickness, the Manual Pavement Design 2017 methode (MDPJ) and Asphalt Institute method. Calculate the parameter sensitivity analysis of overlay thickness for each method to see what parameters cause the different overlay thickness. Based on the results of the analysis, the temperature adjustment factor and critical period must be considered in designing the conditions in Indonesia. The value of the TAF in MDPJ 2017 method based on an annual mean temperature of Indonesia that is 41 ° C, while the average temperature in every region in Indonesia vary considerably so this parameter could not be equal for each area. Asphalt Institute method sets the four time periods, while MDPJ 2017 method using only two time periods of testing. This is due to the time of testing is influenced by the season factor, where Indonesia has only two seasons. Therefore, although the method of Asphalt Institute produces overlay thickness that is thinner, but in this research recommended using the MDPJ 2017 method for the conditions in Indonesia.